ANALISIS PEMAHAMAN MAHASISWA TINGKAT II TERHADAP PENGGUNAAN UNGKAPAN NDESU ATAU NODA - Aziz, Yendi Zulfa Aziz Zulfa; Basri, Merri Silvia Basri Silvia; Nimashita, Hana Nimashita Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research is to know how good is the comprehension of second semester students of Japanese Language Study Program FKIP University of Riau in using Ndesu expression. In this research, the writer use descriptive method with quantitative approach. Object of this research is second semester students of academic year 2014/2015 Japanese Education Study Program FKIP University of Riau that consists of 39 students, but only 22 students are ready to join in collecting the data. The writer use questionnaire and test as the data collecting technique in this research. Questionnaire given to the students contains students’ prior knowledge about ndesu expression, and test that given to the students contains questions about ndesu expression. The result of the questionnaire and the test are manually calculated to know the result of the questionnaire and the test.The result of this research is respondents understand with the function of ndesu expression in asking the reason and mentioning the reason, and respondents not understand with the function of the ndesu expression in asking the explanation and (先触れ。前置き)sakibure maeoki.Keywords : Modality, Setsumei, Ndesu or Noda, Comprehension